Assistance of Posyandu Service Capacity Building Program in Cancung and Sumberbendo Villages, Bojonegoro Regency - Sunariyo, Sunariyo; Hidayati, Niswatin Nurul (IDFoS Indonesia, 2021)
The purpose of the assistance carried out was to improve posyandu services for infants and children, as an effort to prevent the condition of undernourished children under five. The expected result of the program was an increase in the quality of posyandu services in Cancung and Sumberbendo Villages. The expected immediate results were the implementation of increased knowledge and ability of posyandu cadres to facilitate, rehabilitation of children’s nutrition with a Positive Deviance approach, the availability of posyandu service facilities and support from relevant government agencies. From the assistance that had been carried out, there were several outputs and activities carried out, including the support from the village, sub-district and related offices, where this was supported by several activities carried out, they were program coordination with sub-district and district, meetings with villagers, program dissemination, and contribution-raising FGDs. Then, the increased knowledge and ability of posyandu cadres to carry out health promotion was achieved by several activities, including positive deviance training, infant and child feeding training, and public speaking training for cadres. In addition, there were activities to rehabilitate children’s nutrition with a positive deviant approach which were achieved with FGDs of mothers and grandmothers, positive deviant family assessments, FGDs for analysis of research results, FGDs for determining welfare levels, nutrition post, mome visits, health campaigns, dissemination, routine assistance. Furthermore, the existence of supporting facilities for Posyandu services and health promotion facilities were supported by several activities which included the provision of posyandu promotion media, provision of posyandu service facilities, and monitoring and evaluation.